2003
DOI: 10.1016/s0001-2092(06)60664-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Chain of Custody Evidence Handling in Forensic Cases

Abstract: IN VIOLENCE AND ABUSE CASES, perioperative nurses are responsible for protecting victims' rights and ensuring that potential evidence of a crime is not compromised. FORMAL EDUCATION for nurses now is available in the relatively new field of clinical forensic nursing. PERIOPERATIVE NURSES should ensure that they receive proper education in identifying, collecting, and securing evidence and maintaining the chain of custody, whether through a formal education process or by reviewing protocols at their facilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 1 publication
0
16
0
2
Order By: Relevance
“…Her adli olguda oldugu gibi adli olgu bildirimi yapildiktan sonra cinsel saldinya ugrayan kiçilerin aydinlatilmiç onamlan alinarak, tecrübeli bir hekim tarafmdan beden muayenesi sirasmda vajinal, oral ve/veya anal ömekler toplanmalidir [29]. Her adli olguda oldugu gibi adli olgu bildirimi yapildiktan sonra cinsel saldinya ugrayan kiçilerin aydinlatilmiç onamlan alinarak, tecrübeli bir hekim tarafmdan beden muayenesi sirasmda vajinal, oral ve/veya anal ömekler toplanmalidir [29].…”
Section: Adli Olgudan Biyolojik Materyallerin Toplanmasiunclassified
“…Her adli olguda oldugu gibi adli olgu bildirimi yapildiktan sonra cinsel saldinya ugrayan kiçilerin aydinlatilmiç onamlan alinarak, tecrübeli bir hekim tarafmdan beden muayenesi sirasmda vajinal, oral ve/veya anal ömekler toplanmalidir [29]. Her adli olguda oldugu gibi adli olgu bildirimi yapildiktan sonra cinsel saldinya ugrayan kiçilerin aydinlatilmiç onamlan alinarak, tecrübeli bir hekim tarafmdan beden muayenesi sirasmda vajinal, oral ve/veya anal ömekler toplanmalidir [29].…”
Section: Adli Olgudan Biyolojik Materyallerin Toplanmasiunclassified
“…(24) Other studies have found no such associations. (25) It was unknown if the documented injuries, both genital and nongenital, "Sato, I., Nakamura, A., Ujiie, K., Yukawa, N., Nakajima, Y. A sandwich enzyme-linked immunosorbent assay for ABO blood typing of semen by using anti-p 84 monoclonal antibody as a marker of blood group substance in semen.…”
Section: Treatment and Documentation Of Injuriesmentioning
confidence: 99%
“…Department of Justice, 2004, p.18). Biological and physical evidence gathered during the forensic medical exam may include hair combings, swabbing, finger nail scrapings, trace material such as debris from the crime scene and clothing (Evans, Stagner, & Rooms, 2003; U.S. Department of Justice, 2004).…”
Section: Forensic Medical Exam and Evidence Collectionmentioning
confidence: 99%